Optical Passive Athermalization For a Separated Two-Lens Thermal Imaging System (Damascus University Journal for engineering sciences, 2026)
Thermal imaging systems are widely used because of their continued reduced cost and increased reliability. This is mainly due to the development of Uncooled Focal Plane Arrays FPA which eliminated the need for mechanical scanners and coolers. But these systems suffer from thermal focal shift, where refractive indices change with temperature, which leads to image plane shift away from the surface of the detector resulting in blurred images. This paper proposes an optical design for a two-lens thermal imaging system that is athermalized using the optical passive method. The proposed design is small and light. To the best of our knowledge, these calculations are not carried out in the literature.
Keywords: Thermal Imaging Systems; –Infrared Radiation; –Athermalization; Optical Design; Paraxial Calculations; Uncooled Focal Plane Arrays; Thermal Focal Shift